Peran Cek Bagus dan Cek Ayu Sebagai Brand Ambassador Dalam Mempromosikan Budaya Palembang - M. Farhan davis saputra; Hamidah Hamidah; Muzaiyanah Muzaiyanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of cultural promotion carried out by Cek Bagus and Cek Ayu Palembang in promoting Palembang culture. Focusing on the promotional activities during the 2025 JKPI (Indonesian Heritage City Network) event in Yogyakarta, this study employed descriptive qualitative techniques. All data were collected through direct participant observation and visual analysis documentation during the event. This study employed Stuart Hall's theory of cultural representation to understand the gradual formation of cultural meaning. The results show that the cultural promotion carried out by Cek Bagus and Cek Ayu Palembang during the event included Palembang creative dance, Palembang Bahasa singing, Palembang Kuntau martial arts, traditional costume parades, and several other cultural promotional activities. This study focuses on the constructionist perspective, where cultural meaning is formed through symbols and narratives of objects produced, thus generating new meanings without eliminating old ones. It also focuses on a reflective approach that views cultural meaning as authentic or distinctive to the culture that already exists.